Mady Frangella: capstone - Frangella, Mady, artist (Colorado State University. Libraries, 2024)
The artist's statement: The majority of my art follows the introspective journeys I embark on when I challenge what I feel and how I feel it. My mental health is the biggest pool of subjectivity from which I pull from and explore in different mediums both traditionally and digitally. I am who I am because of all that I have lived through. I use my art to make others believe that their feelings do not isolate them, and, instead, create deeper connections with those who understand where they've been. My inspiration lies in personifying the struggles of daily life for those with mental illnesses and learning disabilities, such as myself, creating understanding and empathy between all of us humans. My subjectivity is not limited to navigating mental health throughout my young life, but also involves my passion for storytelling and the power of words. There is fire within me to use my artistic power to breathe life into stories that are eager to be told. I am for an art in which the imagination runs free and has no boundaries. I'm driven to create art that opens doors and windows to the world to reject isolation, ensuring that no one is ever really alone. Whether it's exploring Adobe Creative Suite applications for graphic design and landscape paintings or 3D modeling in Blender, I find my most authentic self-expression through electronic art mediums. I’ve found that these have the most accessible UX/UI for my learning disabilities: ADHD and autism. I love working in a 3D application on the computer the most because I think completely in 3-dimensional spaces and find the user interface is the most instinctive and natural for the way that my brain works. By pouring my insides out into the physical world, I am releasing my fear of vulnerability and any hold that societal pressures have on me to be someone I’m not while eliminating boundaries that separate me from others.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: electronic art